2015
DOI: 10.1530/eje-15-0451
|View full text |Cite
|
Sign up to set email alerts
|

The growth response to GH treatment is greater in patients with SHOX enhancer deletions compared to SHOX defects

Abstract: Objective: Short stature caused by point mutations or deletions of the short stature homeobox (SHOX) gene (SHOX haploinsufficiency (SHI)) is a registered indication for GH treatment. Patients with a SHOX enhancer deletion (SED) have a similar phenotype, but their response to GH is unknown. It is uncertain if duplications of SHOX or its enhancer (SDUP) cause short stature. This study aimed to describe the clinical characteristics and growth response to GH treatment in patients with aberrations of SHOX and its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…Heterozygous deletions of the downstream and upstream enhancer of SHOX cause a similar phenotype as defects of SHOX itself (144,145,146,147,148,149), and the growth response to GH treatment is even better in children carrying a deletion of the SHOX enhancer than in carriers of a SHOX defect (150). The consequences of increased copies of SHOX are less clear (146,150,151,152,153).…”
Section: Genetic Defects Of Intracellular Pathwaysmentioning
confidence: 99%
“…Heterozygous deletions of the downstream and upstream enhancer of SHOX cause a similar phenotype as defects of SHOX itself (144,145,146,147,148,149), and the growth response to GH treatment is even better in children carrying a deletion of the SHOX enhancer than in carriers of a SHOX defect (150). The consequences of increased copies of SHOX are less clear (146,150,151,152,153).…”
Section: Genetic Defects Of Intracellular Pathwaysmentioning
confidence: 99%
“…SHOX downstream deletions may be associated with a broad clinical spectrum because Chen et al [2009] documented a prominent phenotype in patients with such deletions. Furthermore, Donze et al [2015] reported that patients with enhancer deletions were equally short as those with SHOX intragenic defects but were less disproportionate and showed better responses to growth hormone (GH) therapy. Benito-Sanz et al [2011] suggested that SHOX duplications are often associated with relatively mild phenotypes.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…However, long-term outcomes of GH treatment need to be evaluated in future studies. Since Donze et al [2015] reported that GH treatment was more effective in patients with enhancer deletions than in those with intragenic abnormalities, patients should be classified according to their mutation types. In addition, while Ogata et al [2001b] suggested that gonadal suppression therapy may be useful to prevent the development of Madelung deformity in female patients, the outcome of this therapy remains to be investigated.…”
Section: Treatment Of Patients With Shox Abnormalitiesmentioning
confidence: 99%
“…A 40 kb hosszúságú SHOX gén a humán genomban az X-(Xp22.3) és Y-(Zp11.3) kromoszómák pszeudoautoszomális régiójában (PAR1), a nemi kromoszómák telomerjeitől 500 kb-nyi távolságra talál-ható [5][6][7][8]. Elhelyezkedésének köszönhetően elkerüli az X-kromoszóma inaktiválódását, így a hibáihoz tartozó betegségek öröklődésmenetére a pszeudoautoszomális mód jellemző [9], ezért a gén kifejeződésének mértéke a férfi és a női szervezetben megegyezik.…”
unclassified